2019
DOI: 10.1016/j.cortex.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Processing number and length in the parietal cortex: Sharing resources, not a common code

Abstract: A current intense discussion in numerical cognition concerns the relationship between the processing of numerosity and other non-numerical quantities. In particular, it is a matter of debate whether number and other quantities (e.g., size, length) are represented separately in the brain or whether they share a common generalized magnitude representation. We acquired high-resolution functional MRI data while adult subjects engaged in a magnitude comparison task involving either numerosity (i.e., which of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Previous studies showed that when subjects process words that refer to common concrete objects, the implied average size or sound are individually separately represented in visual and auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). These results are in line with a recent proposal (Borghesani and Piazza, 2017) that suggests that semantic representations of concrete words can be conceived as points in multidimensional spaces where different dimensions represent the different characteristics that define the meaning of a word.…”
Section: Sensory Regions Represent Distances Travelled Along Separatesupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies showed that when subjects process words that refer to common concrete objects, the implied average size or sound are individually separately represented in visual and auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). These results are in line with a recent proposal (Borghesani and Piazza, 2017) that suggests that semantic representations of concrete words can be conceived as points in multidimensional spaces where different dimensions represent the different characteristics that define the meaning of a word.…”
Section: Sensory Regions Represent Distances Travelled Along Separatesupporting
confidence: 80%
“…In a recent proposal (Borghesani and Piazza, 2017), starting from the assumption that semantic representations of concrete words (e.g., "tomato") are points in multidimensional spaces where each dimension represents specific characteristics of the object referred to by the word (e.g., red color, roundish shape, small size), we suggested that the different dimensions are coded both conjunctively (in convergence zones, and here demonstrated through spatialcodes), but also separately, in the same brain regions that respond to those features when the objects are physically presented. In support of the idea we and others found that when subjects process words that refer to concrete objects the implied average size or sound associated are indeed separately represented in visual or auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). Here we looked at the whole brain level to reveal whether and where separate representational maps of size and pitch existed.…”
supporting
confidence: 83%
“…Importantly, the common magnitude system would predict not only common brain activation patterns but also a common representational code across quantities. Despite some evidence for similar neural activation patterns when processing these distinct quantities, there is no evidence for a common representational code for both quantities-at least in respect to space and number (Borghesani et al, 2018). Given that timing appears less connected to both space and number, it is unlikely that a common representational code exists between space and timing or number and timing.…”
Section: Patterns Of Neural Activationmentioning
confidence: 96%
“…In related work, others have noted overlapping representations in parietal BOLD signals for one-dimensional metrics in distinct domains, such as spatial, temporal and social distance (Parkinson et al, 2014). However, it has been debated whether these results imply a common representation or simply shared resources in the parietal cortex (Borghesani et al, 2019).…”
Section: [Permission Pending For Reprints]mentioning
confidence: 99%